Resort Design with a Sustainable Architectural Approach in Serdang Bedagai Regency - Sinta Marito Br. Panjaitan; Ar. Melly Andriana; Cut Nuraini (Sean Institute, 2026)
This study develops a sustainable coastal resort design at Pantai Mangrove, Serdang Bedagai, as a response to the rapidly growing tourism pressure in an area lacking environmentally responsible facilities. A sustainable architectural approach grounded in biophilic design is applied to translate human–nature connectivity into spatial strategies and building performance. The design principles include the use of locally sourced, low-carbon materials; optimization of cross-ventilation and natural lighting; integration of vegetation for both aesthetic and ecological functions; efficient rainwater and wastewater management; and site planning that respects the sensitivity of coastal ecosystems. The design methodology encompasses site observations, space programming, and environmental standards review to ensure measurable performance outcomes. The resulting proposal features an organically inspired morphology derived from seashell and wave forms, reinforcing the identity of the coastal setting while enhancing visitor comfort, reducing operational energy loads, and supporting the local economy. This design has the potential to serve as a replicable model for sustainable coastal tourism development in North Sumatra.